2020
DOI: 10.1161/hypertensionaha.119.13528
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Systolic Blood Pressure at Moderate Workload Is Linearly Associated With Coronary Disease Risk in Healthy Men

Abstract: There is no consensus on the definition of an exaggerated increase in systolic blood pressure (SBP) during exercise. The aim was to explore a potential threshold for exercise SBP associated with increased risk of coronary heart disease (CHD) in healthy men, using repeated exercise testing. 2,014 healthy Caucasian male employees were recruited into the Oslo Ischemia Study during early 1970s. At follow-up seven years later, 1,392 men were still considered healthy. A bicycle exercise test at 100W workload was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…However, it remains unclear which of these novel indices is the most accurate predictor of incident CVD, as head-to-head data from outcome studies are lacking. In addition to longitudinal BP indices covered by this review, BP measurements taken during exercise and antihypertensive therapy could also provide incremental predictive value over conventional "present" BP [66][67][68]. Nevertheless, until additional data become available, more emphasis should be put on assessing the clinical feasibility of these BP indices.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear which of these novel indices is the most accurate predictor of incident CVD, as head-to-head data from outcome studies are lacking. In addition to longitudinal BP indices covered by this review, BP measurements taken during exercise and antihypertensive therapy could also provide incremental predictive value over conventional "present" BP [66][67][68]. Nevertheless, until additional data become available, more emphasis should be put on assessing the clinical feasibility of these BP indices.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, high BP response to exercise appears to predict future development of hypertension in young athletes even after adjustment with resting BP [7]. Interestingly, Mariampillai et al recently reported that exercise systolic BP at moderate workload is linearly associated with coronary disease risk in healthy middle-aged men independently of resting BP [29]. Altogether, it appears that even though EEBP may be a physiological compensatory mechanism at least in welltrained athletes, it may also reveal failing compensatory mechanisms or hypertensive tendency beyond resting BP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we chose 100W analogous to the suggested workload to define and assess non-invasive exercise hypertension (or exaggerated blood pressure response) during bicycle ergometry. 24 ExRHC was performed on a bicycle ergometer directy after the resting measurements, either in patients without (<25 mm Hg) or moderately elevated mPAP (25-35 mm Hg) at rest. PH at rest was defined according to the suggestions of the Task Force of the 6th World Symposium on Pulmonary Hypertension, during which the mPAP threshold was lowered to 20 mm Hg.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…100W has also been suggested as a threshold to determine exaggerated (peripheral) blood pressure response during regular bicycle ergometry. 24 Furthermore, peak performance of 100W was deemed to represent sufficient cardiorespiratory fitness for our elderly population. With higher workload, the probability of exPH may further decrease, represented by decreasing exmPAP, exPAWP and exPVR.…”
Section: Step 2 Formation Of a Combinatorial Diagnostic Score For Exphmentioning
confidence: 99%